1997
DOI: 10.1021/om9705214
|View full text |Cite
|
Sign up to set email alerts
|

Metal−Phosphorus Bonding in Fe(CO)4PR3 Complexes. A Density Functional Study

Abstract: Fe(CO) 4 PR 3 complexes have been studied for R ) H, Me, Ph, OMe, F, i-Pr, and NC 4 H 4 using density functional methods. The Fe-PR 3 bond has been analyzed in terms of steric and electronic effects. The results obtained show that the main contribution to the bond stems always from the σ donation, but phosphines can be classified into three groups depending on the relative magnitude of the π-back-donation contribution. Thus, PMe 3 , PPh 3 , and P(i-Pr) 3 can be considered as σ-donor ligands, PF 3 and P(NC 4 H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
45
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 70 publications
8
45
0
Order By: Relevance
“…Experimental evidence and qualitative molecular orbital considerations suggest that strong p-accepting ligands prefer the equatorial position of trigonal bipyramidal complexes containing d 8 number of quantum chemical studies of complexes Fe(CO) 4 L (L = N 2 [18], H 2 [19], PR 3 [20], C 2 H 4 [21] and C 2 H 2 [22]). Experimental evidence and qualitative molecular orbital considerations suggest that strong p-accepting ligands prefer the equatorial position of trigonal bipyramidal complexes containing d 8 number of quantum chemical studies of complexes Fe(CO) 4 L (L = N 2 [18], H 2 [19], PR 3 [20], C 2 H 4 [21] and C 2 H 2 [22]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental evidence and qualitative molecular orbital considerations suggest that strong p-accepting ligands prefer the equatorial position of trigonal bipyramidal complexes containing d 8 number of quantum chemical studies of complexes Fe(CO) 4 L (L = N 2 [18], H 2 [19], PR 3 [20], C 2 H 4 [21] and C 2 H 2 [22]). Experimental evidence and qualitative molecular orbital considerations suggest that strong p-accepting ligands prefer the equatorial position of trigonal bipyramidal complexes containing d 8 number of quantum chemical studies of complexes Fe(CO) 4 L (L = N 2 [18], H 2 [19], PR 3 [20], C 2 H 4 [21] and C 2 H 2 [22]).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidence and qualitative molecular orbital considerations suggest that strong p-accepting ligands prefer the equatorial position of trigonal bipyramidal complexes containing d 8 metals, while r-donor ligands prefer axial coordination sites [16±17]. This model was studied by a limited number of quantum chemical studies of complexes Fe(CO) 4 L (L = N 2 [18], H 2 [19], PR 3 [20], C 2 H 4 [21] and C 2 H 2 [22]). However, no systematic and comparative theoretical work with respect to a wider range of such complexes has been published so far.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Schmid et al [16] and González-Blanco and Branchadell [17] have shown that PH 3 cannot model the PPh 3 when processes that involve the cleavage or formation of M-P bonds are involved. Gleich et al [18] used a combined quantum mechanical/molecular mechanical (QM/MM) approach to determine the regioselectivities in the rhodium-catalyzed hydroformylation of propene.…”
mentioning
confidence: 99%
“…19 While electron acceptor ability of a molecule is related with E LUMO , E HOMO represents σ -donor ability. 31,32 When we move from O to Se, the energy of LUMO decreases and that of HOMO increases. The energies of HOMO and LUMO for the compounds 2-4 indicate that the relative order of σ -donation is 4 > 3 > 2.…”
Section: Theoretical Calculationsmentioning
confidence: 99%